Stearoyl‐CoA desaturase and carotenoids concertedly enhance the resistance of pearl oyster Pinctada fucata to high temperature stress. (26th August 2020) - Bai, Lirong; Meng, Zihao; Liu, Baosuo; Yang, Deguo; Yu, Dahui
Abstract: We characterized a novel stearoyl‐CoA desaturase gene from Pinctada fucata, named PfSCD, and investigated the expression levels in various tissues of high and low carotenoid contents (orange and white groups) and the responses to high temperature stress (from 26°C to 30°C). The complete cDNA sequence consisted of 1, 576 bp with a 945 bp open reading frame encoding 315 amino acid residues; it included four transmembrane domains and three conserved histidine‐box motifs. Pinctada fucata was clustered with molluscan SCD genes. The relative expression level of PfSCD mRNA, total carotenoid content (TCC) and total antioxidant capacity (TAC) was greatly up‐regulated in orange group as compared with the white, with the highest in hepatopancreas and followed by gonad tissue and the lowest in foot. The relative expression level of PfSCD increased first and then decreased during the stress period of temperature 30°C from 0 to 96 hr in the orange group with the peaks at 6 and 12 hr. Meanwhile, TCC and TAC decreased gradually during the stress, with a significant increase at 6 hr in the hepatopancreas and gonadal tissues, respectively, in the orange group, corresponding to the rise of PfSCD at 6 hr. It suggested that carotenoids can be up‐regulated by PfSCD . Moreover, the positive correlations of PfSCD mRNA with TCC and TAC were both disrupted under the high temperature stress. These findings suggested that SCD and carotenoids can be up‐regulated by each other and concertedly enhance the resistance of the oyster to high temperature stress.